Family disability, poverty and parenting stress: Analysis of a cross-sectional study in Kenya - Xanthe Hunt; Christina Laurenzi; Sarah Skeen; Leslie Swartz; Phillip Sundin; Robert E. Weiss; Mark Tomlinson (African Journal of Disability, 2021)
Background: Households with a disabled member, be they a caregiver or a child, are poorer than households not affected by disability. Poverty, caregiving as a person with a disability and being the caregiver of a child with a disability can lead to increased parenting stress.